Program for PDA educational organizer / Ng Heang Tong - Ng, Heang Tong (2004)
PalmForce Organizer system is a PDAs based system aimed at helping the PDA user to manage their daily operation or work. The purpose of PalmForce is to integrate all the useful organizer such as financial organizer, health organizer, personal organizer and educational organizer into one package so that the user won't have to look for the four types of organizers. This system provides user a very convenient use as with this system, the user can plan for their educational information, financial information, personal information and health informatioprototype model approachn in just one system. The prototype model approach is selected for the development of PalmForce. This method is adopted because simple and ease of implementing. In addition, testing is performed in every stage and it may provide a chance to enhance the previous version of the product in every phase. Through the system development life cycle, system methodology is adopted to understand the current problem situation. Careful analysis and research has been conducted to determine the feasibility of the · system and what is required of it. The system requirements are identified, translated into design and finally implemented via coding. The finished system is evaluated to meet the system objectives and requirements specification. Practically, the PalmForce is program using J2ME technology and developed on Microsoft Windows XP Professional platform. The development tool is Borland JBuilde 9.0.